Description of an extant salamander from the Gulf Coastal Plain of North America: The Reticulated Siren, Siren reticulata - Graham, Sean P.; Kline, Richard; Steen, David A.; Kelehear, Crystal (PLOS ONE, 2018)
The salamander family Sirenidae is represented by four extant species that are restricted to North America. Sirens are abundant throughout the southern United States and are among the world’s largest amphibians, yet the biology, ecology, and phylogeography of this group is poorly-known. In this study we use morphological and genetic evidence to describe a previously unrecognized species from southern Alabama and the Florida panhandle. We name this species the Reticulated Siren, Siren reticulata. Future studies will enable more precise phylogenetic information about S. reticulata and will almost surely reveal additional undescribed species within the family.